Relationships between Nursing Students’ Attitudes Toward the Nursing Profession, Fear of COVID-19, and Intolerance of Uncertainty: A Cross-sectional Study - Terzi, Banu; Azizoğlu, Fatma; Seven, Çağla (UI Scholars Hub, 2023)
Background: Nursing students were caught unprepared for the COVID-19 pandemic. Both the inability to control the epidemic and the interruption of education caused students to experience fear, anxiety, and uncertainty. This study investigates the relationships between nursing students’ attitudes toward the nursing profession and their fear of COVID-19 and intolerance of uncertainty. Methods: This cross-sectional study included 727 nursing students who were members of the Student Nurses Association and who volunteered to participate in the research. Research data were collected using the Student Information Form, The Fear of COVID-19 Scale, the Intolerance of Uncertainty Scale (IUS-12), and the Attitudes Towards Nursing Profession Scale. Results: Statistically significant positive relationships were found between the fear of COVID-19 and intolerance of uncertainty levels (p < 0.01) and attitudes toward the nursing profession in general (p < 0.05). Conclusions: Students had a mid-level of fear of COVID-19, a high level of intolerance of uncertainty, and positive attitudes toward the nursing profession. To decrease nursing students’ intolerance of uncertainty during pandemic-like crisis situations, preventive and reformative activities should be planned.